Asean Dalam Mendorong Negara Permanent 5 Untuk Mengaksesi Southeast Asian Nuclear Weapon Free Zone (Seanwfz) - Seftina Kuswardini (Journal of Islamic World and Politics, 2018)
This paper contains the dynamics of the establishment of nuclear weapons free zone form by ASEAN in the form of SEANWFZ treaty as an effort to maintain regional security of Southeast Asia. But in its implementation there are some obstacles and the most seats is the approval of the State Permanent 5 (P5). The five countries continue to delay reviewing the contents of the agreement until there are several reservations in the form of application zone, ship transit rights, sovereignty and negative security guarantees. Moreover, the problem of coverage of the region consisting of Exclusive Economic Zone (ZEE) of several ASEAN countries in the view is not yet clear related to claim of South China Sea. ASEAN continues to push the five nuclear states in a period of less than two decades by way of negotiation and dialogue. But in essence it will explain the dynamics of SEANWFZ itself, the various reservations that make P5 not willing to access SEANWFZ and the South China Sea settlement as one of the efforts in encouraging China and some P5 countries to access SEANWFZ. Tulisan ini berisi tentang dinamika pembentukan kawasan bebas senjata nuklir yang dibentuk (dibentuk) oleh ASEAN dalam bentuk traktat SEANWFZ sebagai upaya untuk menjaga keamanan regional Asia Tenggara. Namun pada implementasinya terdapat beberapa hambatan dan yang paling kursial yaitu persetujuan dari Negara Permanent 5 (P5). Kelima Negara tersebut terus menunda untuk mengkaji lebih dalam lagi isi-isi dari perjanjian hingga timbul beberapa reservasi berupa zona aplikasi, hak transit kapal, kedaulatan dan jaminan keamanan negatif. Terlebih lagi masalah cakupan wilayah yang terdiri dari Zona Ekonomi Ekslusif (ZEE) beberapa Negara ASEAN dianggap belum jelas terkait klaim Laut China Selatan. ASEAN terus mendorong kelima Negara pemilik nuklir tersebut dalam kurun waktu kurang lebih dua dekade dengan cara negosiasi dan dialog. namun pada intinya tulisan ini akan menjelaskan tentang dinamika SEANWFZ sendiri, berbagai reservasi yang membuat P5 belum bersedia mengaksesi SEANWFZ dan penyelesaian Laut China Selatan sebagai salah satu upaya dalam mendorong China dan beberapa Negara P5 untuk mengaksesi SEANWFZ.